Air Quality of a Parking Building in Makassar (A Case Study of Bosowa Tower Parking Building) - Nasrul Kulle; Baharuddin Hamzah; Rosady Mulyadi (EPI International Journal of Engineering, 2021)
This study aims to determine the level of air quality in the parking building based on the pollution content in it (CO, CO2, HCHO and, VOC), to analyze the effect of the weather, intensity of motorized vehicle traffic, and surface elevation to the air quality. The dependent variable is the level of air pollution. The research sample is the Makassar Bosowa Tower Parking Building, data collection was carried out by direct measurement and observation in 12 days from November 24th till December 17th. The research was done using the comparative method, The data processed using the Mann-Whitney difference test, and the Spearman correlation test using SPSS application. The results showed that the average CO levels had exceeded the limit of good air quality, the average of CO2 levels was still within the limits for good air quality, and the average of HCHO and VOC levels were mostly within the limits for good indoor air quality, according to The Indonesia Minister of Health Regulation Number 1077 in 2011. The result of measurements and tests shows that the changes in the weather do not have a significant effect on the air quality. The amount and the intensity of motorized vehicle traffic affect the air quality, especially during rainy weather.